Morphological and Molecular Characterization of Isolated Probiotic Yeast - Greeshma, K.; Deokar, C. D.; Raghuwanshi, K. S.; Bhalerao, V. K. (International Journal of Bio-resource and Stress Management, 2022)
The Experiment was conducted during 2019 in the research laboratory in the Department of Plant Pathology and Agricultural Microbiology, Post graduate Institute, Mahatma Phule Krishi Vidyapeet, Rahuri, Ahmednagar, Maharashtra, India. The objective of this study was to isolate and characterize probiotic yeast isolated using fermented jowar and bajra cereal grain flours for their efficacy as biocontrol agents. The yeast species isolated on Malt extract agar were morphologically and molecularly identified. The region obtained by PCR analysis with Internal transcribed spacer (ITS) specific primers of fungi was further sequenced and the cultures were confirmed as Saccharomyces cerevisiae and Saccharomyces arboricola by BLAST analysis . The conserved region of the isolate was amplified and the size was found to be of 758 bp for Saccharomyces cerevisiae and 698 bp for Saccharomyces arboricola in agarose gel electrophoresis and visualized through gel documentation. The nucleotide sequence obtained was subjected to Basic Local Alignment Search Tool and data was submitted to NCBI. The accession number obtained for Saccharomyces cerevisiae was MZ068117 and for Saccharomyces arboricola wasMZ068118. The Phylogenetic tree was constructed individually using neighbour joining approach by using Molecular Evolutionary Genetics Analysis (MEGA X) and Motif analysis by using Multiple EM for Motif Elicitation (MEME software) bioinformatics tools of thirty closest species was performed and about five conserved sequences were obtained among the tested strains.